Improvement in Attention Processing After Surgical Treatment in Functional Pituitary Adenomas: Evidence From ERP Study - Cao, Chenglong; Huang, Yujing; Chen, Aobo; Xu, Guozheng; Song, Jian (Frontiers in Neurology, 2021)
Cognitive abilities are impaired in patients with pituitary adenoma. However, the study on attention processing impairment in preoperative patients and attention processing recovery after transsphenoidal adenomectomy is lacking. The study aims to identify the electrophysiological change that relates to the attention processing in pituitary patients before and after treatment. 25 preoperative pituitary patients and 25 follow-up postoperative patients were recruited. 27 healthy controls (HCs) were matched to the patients with age, gender, and education. Event-related potentials were used to investigate the attention processing in the preoperative patients, postoperative patients, and HCs. Across three groups, all emotional stimuli evoked P200 components. Compared with the HCs or postoperative patients, the amplitudes of P200 in the preoperative patients were higher. Moreover, The amplitudes of P200 decreased in the postoperative patients, which were similar to that in the HCs. The attention processing was improved after surgery, but no significant differences were detected between the postoperative patients and HCs. Abnormal hormone levels may be relevant to the factor that impair attention processing. Compared with that of the HCs and postoperative patients, the P200 component elicited by negative stimuli is higher in preoperative patients, which may illustrate compensatory activity after the attention impairments. Furthermore, these data indicate that the improvement in attention processing may be attributed to the amelioration of endocrine disorders. This study shows that the P200 component may be used to diagnose the attention processing in preoperative pituitary patients and prove the improvement of the attention processing in postoperative patients.